Small extracellular vesicles as a multicomponent biomarker platform in urinary tract carcinomas - K, Szeliski; T, Drewa; M, Pokrywczyńska (Frontiers in Molecular Biosciences, 2022)
Extracellular Vesicles are a large group of nano-sized vesicles released by all cells. The variety of possible cargo (mRNAs, miRNAs, lncRNAs, proteins, lipids) and the presence of surface proteins, signaling molecules, and receptor ligands make them a rich source of biomarkers for malignancies diagnosis. One of the groups gathering the most interest in cancer diagnostic applications are Small Extracellular Vesicles (sEVs), with ≤200nm diameter, mainly composed of exosomes. Many studies were conducted recently, evaluating the diagnostic potential of sEVs in Urinary Tract Carcinomas (UTC), discovering and clinically evaluating various classes of biomarkers. The amount of research concerning different types of UTC understandably reflects their incidence. sEVs cargos getting the most interest are non-coding RNAs (miRNA and lncRNA). However, implementation of other approaches like metabolomic and proteomic analysis are also evaluated. Results of many studies indicate that sEVs have an essential role in the cancer process and possess many possible diagnostic and prognostic applications for UTC. The relative ease of obtaining biofluids rich in sEVs (urine, blood) confirms that sEVs are essential for UTC detection in the liquid biopsy approach. A noticeable rise in research quality is observed as more researchers are aware of the research standardization necessity, which is essential for considering the clinical application of their findings.